1998
DOI: 10.1177/135910539800300105
|View full text |Cite
|
Sign up to set email alerts
|

Social Influences and Leisure-time Physical Activity Levels in Young People

Abstract: This study describes the associations between social factors and leisure-time physical activity levels in young people. Important concepts from Bandura's social learning theory and Bourdieu's theory of social position and lifestyles were used as theoretical frameworks. Baseline data were collected from a sample of 827 students (11-14 years old) and their parents in 1979. In 1991, the same students, now aged 23 to 26 years, participated in a follow-up ( N = 514, 62.2 percent of baseline). At the follow-up, fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…Unlike some previous studies (Oygard & Anderssen, 1998;Osler, et al, 2001) we did not detect different impact of SES on physical activity levels in either gender, since among both men and women no socioeconomic inequalities in physical activity were found. Another surprising finding in our study was that more frequent sedentary behaviour (as measured by Internet use and television use) was not associated with the frequency of physical activity, although previous studies have confirmed such link (Marshall, et al, 2004;Gebremariam, et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike some previous studies (Oygard & Anderssen, 1998;Osler, et al, 2001) we did not detect different impact of SES on physical activity levels in either gender, since among both men and women no socioeconomic inequalities in physical activity were found. Another surprising finding in our study was that more frequent sedentary behaviour (as measured by Internet use and television use) was not associated with the frequency of physical activity, although previous studies have confirmed such link (Marshall, et al, 2004;Gebremariam, et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, among women, higher parental education decreased the likelihood of frequent physical activity, while among men parental education increased the likelihood of frequent physical activity. The same pattern was found in a study of young adults by Oygard & Anderssen (1998), who reported an interaction between gender and education, with highly educated females reporting significantly higher leisure-time physical activity levels than less educated females, though the same pattern was not detected among males. Similar gender interaction has been found in a study of adolescents by Mar Bibiloni and colleagues (2012) who found that girls with lower parental educational levels reported higher frequency of sedentary behaviour (though the differences were statistically insignificant), while the same parental educational impact was not detected among boys.…”
Section: The Frequency and Inequalities In Physical Activitysupporting
confidence: 80%
“…Other longitudinal studies have reported similar findings. 35 In the current study, multivariable analyses showed that, compared with peer influences, parental support was less likely to be associated with being active among adolescents. However, where parental support was apparent, being active was associated with support from the same-sex parent.…”
Section: Discussionmentioning
confidence: 49%
“…In her 12-year follow-up study, Øygard [13] found that one of the most important factors associated with PA was its level at baseline (especially in males; in females it was education). An earlier report [14] from our own 15-month experimental intervention confirmed the effectiveness of a programme based on Hellison's model of Teaching Responsibility through PA [15].…”
Section: Introductionmentioning
confidence: 99%